Combined Risk Based Inspection and Fault Tree Analysis for Repetitive 3-Phase Line Piping Leakage at West Java Offshore Topside Facility - Yuliati, Dona; Yuwono, Akhmad Herman; Dhaneswara, Donanta; Asral, D. Rizal (UI Scholars Hub, 2023)
Hydrocarbon releases might result in serious consequences in various aspects. In addition to the contribution to environmental pollution, repetitive leakages need high repair costs. This study aim is to minimize potential repetitive leakage for other typical 3-phase piping systems. We conducted the risk assessment by adopting Risk Based Inspection (RBI) API 581 to identify risk level, calculating piping lifetime, recommended inspection plan and mitigations. The most relevant root causes can be obtained through quantitative Fault Tree Analysis (FTA). Observation and investigation was taken from eight 3-phase piping systems that experienced repetitive leakages. It has been found that the risk level of some piping systems in yellow and red areas with one pipe in an unfit condition. Next inspection and/or mitigation dates as results of RBI calculation shall be conducted to reduce risk levels and prevent leakage cases. FTA shows the most likely events are the sand problem in fluid, high CO2 content, material deficiency, and high fluid velocity. If the root causes are known earlier, preventive mitigation can be conducted to prevent hydrocarbon release in the other 3-phase piping systems, such as application of internal coating, injection corrosion inhibitor or inspection/monitoring program.